The vanishing veins: difficult venous access in a patient requiring translumbar, transhepatic, and transcollateral central catheter insertion - Yaacob, Yazmin; Zakaria, Rozman; Mohammad, Zahiah; Md Ralib @ Md Raghib, Ahmad Razali; Muda, Ahmad Sobri (Universiti Sains Malaysia, 2011)
Central venous catheter placement is indicated in patients requiring long-term therapy. With repeated venous catheterisations, conventional venous access sites can be exhausted. This case illustrates the expanding role of radiology in managing difficult venous access. We present a case of translumbar, transhepatic, and transcollateral placement of central catheter in a woman with a difficult venous access problem who required lifelong parenteral nutrition secondary to short bowel syndrome. This case highlights the technical aspects of interventional radiology in vascular access management.